2022
DOI: 10.1101/2022.05.10.22274890
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biopsychosocial response to the COVID-19 lockdown in people with major depressive disorder and multiple sclerosis

Abstract: BackgroundChanges in lifestyle, finances and work status during COVID-19 lockdowns may have led to biopsychosocial changes in people with pre-existing vulnerabilities such as Major Depressive Disorders (MDD) and Multiple Sclerosis (MS).MethodsData were collected as a part of the RADAR-CNS (Remote Assessment of Disease and Relapse – Central Nervous System) programme. We analyzed the following data from long-term participants in a decentralized multinational study: symptoms of depression, heart rate (HR) during … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…To adequately understand the impact of the pandemic on depression severity, we need longitudinal studies able to include people with a recent history of MDD. Two previous publications (Leightley et al, 2021; Siddi, et al, 2022) using data from the Remote Assessment of Disease and Relapse-Major Depressive Disorder (RADAR-MDD) study (Matcham et al, 2019), explored the depression severity pre-, during, and post-lockdown periods in people with a history of MDD from Spain, UK and the Netherlands, and observed that patients who displayed significant depressive symptoms shortly before the COVID-19 outbreak decreased in their severity between pre- and during the lockdown (Leightley et al, 2021). However, Leightley et al (2021) and Siddi et al (2022) only considered three periods: pre-lockdown, lockdown, and post-lockdown, but the social restrictions during the post-lockdown were in many places lifted gradually and in different stages, which implies significant differences across countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To adequately understand the impact of the pandemic on depression severity, we need longitudinal studies able to include people with a recent history of MDD. Two previous publications (Leightley et al, 2021; Siddi, et al, 2022) using data from the Remote Assessment of Disease and Relapse-Major Depressive Disorder (RADAR-MDD) study (Matcham et al, 2019), explored the depression severity pre-, during, and post-lockdown periods in people with a history of MDD from Spain, UK and the Netherlands, and observed that patients who displayed significant depressive symptoms shortly before the COVID-19 outbreak decreased in their severity between pre- and during the lockdown (Leightley et al, 2021). However, Leightley et al (2021) and Siddi et al (2022) only considered three periods: pre-lockdown, lockdown, and post-lockdown, but the social restrictions during the post-lockdown were in many places lifted gradually and in different stages, which implies significant differences across countries.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous publications (Leightley et al, 2021; Siddi, et al, 2022) using data from the Remote Assessment of Disease and Relapse-Major Depressive Disorder (RADAR-MDD) study (Matcham et al, 2019), explored the depression severity pre-, during, and post-lockdown periods in people with a history of MDD from Spain, UK and the Netherlands, and observed that patients who displayed significant depressive symptoms shortly before the COVID-19 outbreak decreased in their severity between pre- and during the lockdown (Leightley et al, 2021). However, Leightley et al (2021) and Siddi et al (2022) only considered three periods: pre-lockdown, lockdown, and post-lockdown, but the social restrictions during the post-lockdown were in many places lifted gradually and in different stages, which implies significant differences across countries. The regional and local impact of the COVID-19 crisis has been highly heterogeneous with significant implications for crisis management and policy responses ( The Territorial Impact of COVID-19: Managing the Crisis across Levels of Government , n.d.).…”
Section: Introductionmentioning
confidence: 99%